Molecular characterization of severe acute respiratory syndrome (SARS) coronavirus - nucleocapsid protein - Chauhan, Vinita Singh (Kansas State University, 2006)
Severe acute respiratory syndrome (SARS) is caused by an enveloped, positive-stranded RNA virus, the SARS coronavirus (SARS-CoV). Coronaviruses along with the arteriviruses are placed in the order, Nidovirales. Even though nidovirus replication is restricted to the cytoplasm, the nucleocapsid protein (N) of several coronaviruses and arteriviruses, localize to the nucleolus during infection. Confocal microscopy of N protein localization in Vero cells infected with the SARS-CoV or transfected with the SARS-CoV N gene failed to show presence of N in the nucleoplasm or nucleolus. Recombinant N remained cytoplasmic after the addition of leptomycin B (LMB), a drug that inhibits nuclear export. SARS-CoV N possesses a unique lysine-rich domain, located between amino acids 369-389, which possesses several nuclear localization signal (NLS) and nucleolar localization signal (NoLS) motifs. A chimeric protein composed of the 369-389 peptide substituted for the NLS of equine infectious anemia virus (EIAV) Rev protein (ERev) showed no nuclear localization activity. Three negatively charged amino acids, located at positions 372, 377 and 379 in SARS-CoV N were hypothesized to play a role in the loss of nuclear targeting. Substitution of aspartic acid-372 with alanine restored nuclear localization to the chimeric protein. A full-length recombinant SARS-N protein with the alanine-372 substitution localized to the nucleus. Therefore, the presence of an aspartic acid at position 372 is sufficient to retain N in the cytoplasm The mechanistic basis for how aspartic acid-372 interrupts nuclear transport is unknown, but may lie in the electrostatic repulsion with negatively charged amino acids located within the NLS binding pocket of importin-alpha.
Keywords: Severe Acute Respiratory Syndrome; Coronavirus; Nucleocapsid protein; Nuclear localization; Nuclear transport; Biology, Molecular (0307)